COMBINACIONES FUNCIONALES DEL UT MODAL EN PLAUTO Y CICERÓN - García de la Calera Martínez, Roberto (Myrtia, 2000)
It is intended a classification of passages from Plautus and Cicero with ut -modal regarding the sintactical function that the relative ut and its antecedent have (or, on the absence of the latter, the whole subordinate clause). As a result we offer, but with many reservations, five groups (respectively, Adjunct of Manner, Adjunct of Context, Apossition + Reasoning, Defining Disjunct of inner logic and Non-defining Disjunct of inner logic).